Epitaxially Grown Ferroelectric PVDF‐TrFE Film on Shape‐Tailored Semiconducting Rubrene Single Crystal. Issue 22 (24th April 2018) - Lee, Yujeong; Kim, Kang Lib; Kang, Han Sol; Jeong, Beomjin; Park, Chanho; Bae, Insung; Kang, Seok Ju; Park, Youn Jung; Park, Cheolmin
Abstract: Epitaxial crystallization of thin poly(vinylidene fluoride‐ co ‐trifluoroethylene) (PVDF‐TrFE) films is important for the full utilization of their ferroelectric properties. Epitaxy can offer a route for maximizing the degree of crystallinity with the effective orientation of the crystals with respect to the electric field. Despite various approaches for the epitaxial control of the crystalline structure of PVDF‐TrFE, its epitaxy on a semiconductor is yet to be accomplished. Herein, the epitaxial growth of PVDF‐TrFE crystals on a single‐crystalline organic semiconductor rubrene grown via physical vapor deposition is presented. The epitaxy results in polymer crystals globally ordered with specific crystal orientations dictated by the epitaxial relation between the polymer and rubrene crystal. The lattice matching between the c ‐axis of PVDF‐TrFE crystals and the (210) plane of orthorhombic rubrene crystals develops two degenerate crystal orientations of the PVDF‐TrFE crystalline lamellae aligned nearly perpendicular to each other. Thin PVDF‐TrFE films with epitaxially grown crystals are incorporated into metal/ferroelectric polymer/metal and metal/ferroelectric polymer/semiconductor/metal capacitors, which exhibit excellent nonvolatile polarization and capacitance behavior, respectively. Furthermore, combined with a printing technique for micropatterning rubrene single crystals, the epitaxy of a PVDF‐TrFE film is formed selectively on the patterned rubrene with characteristic epitaxial crystal orientation over a large area. Abstract : Epitaxially grown ferroelectric poly(vinylidene fluoride‐ co ‐trifluoroethylene) (PVDF‐TrFE) thin film is fabricated on semiconducting rubrene single crystal produced via physical vapor deposition. Highly oriented lamellae with two degenerated orientations are explained by the crystallographic lattice match between PVDF‐TrFE and rubrene. A patterning technique allows the fabrication of micropatterns of the rubrene crystal and controls the orientations of the epitaxial crystals.